Perpindahan Panas Dinding Pemodelan CFD di dalam Ruang Bakar menggunakan ANSYS forte - Trisna Setyawan (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2023)
Heat transfer in diesel engines is known to affect engine efficiency and emissions. Increased heat transfer to the combustion chamber walls reduces the pressure in the cylinder and the average gas temperature, which reduces the work transferred to the piston per cycle. Therefore, the amount of heat transfer in an engine largely depends on the efficiency of the engine. Changes in gas temperature due to heat loss from the combustion chamber also affect the formation of pollutant emissions. Higher temperatures in the cylinder promote NOx emissions, while lower temperatures in the cylinder create Particulate matter in the exhaust. Engine heat transfer is important, so engine heat transfer results must be accurately estimated.